Research on developmental language disorders in the Spanish-speaking population - Igualada, Alfonso (Revista de Investigación en Logopedia, 2021)
The specific language Impairment (SLI), also known as developmental language disorder (DLD), presents in the population through severe difficulties in the comprehension and/or expression of language that affect their quality of life and pose a barrier to academic progression and access to employment. The recent shift in its conceptualization and diagnosis in the Anglo-Saxon context towards the concept of DLD (Bishop, Snowling, Thompson, Greenhalgh, Catalise-2 Consortium, Adams,.... & Boyle, 2016 and 2017) has driven the modification of clinical practices, such as the modification of exclusion criteria related to IQ, and the use of this categorization in the scientific literature. This change in the Anglo-Saxon context motivates the review of the state of the art in the Spanish-speaking context in a specific field of the speech and language therapy such as the DLD intervention. The advances in the knowledge about the processes and methodologies of evaluation of SLI/DLD, as well as the historical process of change in the conceptualization of the disorder motivate an analysis of these aspects in the Spanish-speaking clinical and scientific community, since this community shares a network of information conveyed by a common language.
Keywords: Developmental language disorders; Specific language impairment